WORKING ON TEXT PROBLEMS IN PHYSICS LESSONS - Berkinov Alisher Abdurashidovich (American Journals Publishing, 2024)
By solving problems, children get acquainted with facts that are important in the field of knowledge and education. For example, the content of many issues solved in primary classes includes the work of children and adults, the achievements of our country in the national economy, technology, science and culture. The process of solving problems has a positive effect on the mental development of students in a certain method.
Keywords: Problem, methods, analysis and content, clarification, generalization, comparison, condition of the problem, component